1998
DOI: 10.1176/ajp.155.5.630
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Posttraumatic Stress Disorder and Depression Following Trauma

Abstract: Major depression and PTSD are independent sequelae of traumatic events, have similar prognoses, and interact to increase distress and dysfunction. Both should be targeted by early treatment interventions and by neurobiological research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
510
9
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 861 publications
(573 citation statements)
references
References 39 publications
43
510
9
11
Order By: Relevance
“…Thus those patients who drop out might well be at relatively low risk for injury-related PTSD, although loss of memory was not a significant predictor of dropout in the present study. A study by Shalev et al that showed fewer PTSD symptoms among those who dropped out coincides with this view (11). However, O'Donnell et al found higher levels of anxiety and depression among those who dropped out (16).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus those patients who drop out might well be at relatively low risk for injury-related PTSD, although loss of memory was not a significant predictor of dropout in the present study. A study by Shalev et al that showed fewer PTSD symptoms among those who dropped out coincides with this view (11). However, O'Donnell et al found higher levels of anxiety and depression among those who dropped out (16).…”
Section: Discussionmentioning
confidence: 83%
“…Recent longitudinal studies of PTSD have included many different groups of subjects, such as exposed disaster workers (1), refugees (2), a community sample (3), survivors of terrorists attacks (4), soldiers hospitalized following serious combat injury (5), patients with myocardial infarction (6), and victims of sexual and physical assault (7). Above all, longitudinal studies of patients following severe injury, especially those involved in motor vehicle accidents (MVAs), comprise one of the largest number of population samples studied (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Objectives Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Rothbaum, Foa, Riggs, Murdock, and Walsh (1992), Orcutt, Erickson, and Wolfe (2004), Blanchard et al (1996), Ehlers, Mayou, and Bryant (1998) and Shalev et al (1998) also support this assumption in their findings that in regards to change over time, symptom rates of PTSD decrease after the initial exposure to the trauma. Therefore, I hypothesize that length of time since the affair took place should be related to levels of trauma.…”
Section: Variables That Predict Level Of Traumamentioning
confidence: 60%
“…Gradually, the field has come to see the central importance of trauma in many conditions, including psychosis (Kelleher et al, 2013), depression (Shalev, Freedman, Peri, & Brandes, 1998), borderline personality (MacIntosh, Godbout, & Dubash, 2015), and the recent conception of developmental trauma disorder (Rahim, 2014).…”
Section: Rethinking the Field: A Radical Approach (Birrell)mentioning
confidence: 99%